Disability, Happiness and the Welfare State Finland and the Nordic Model - Katsui, Hisayo; Laitinen, Matti T.; Katsui, Hisayo; Laitinen, Matti T. (Oxford Taylor & Francis, 2024)
This book looks at disability as an evolving social phenomenon. Disability is created through the interaction between persons with impairments and their environment. Exploring these experiences of persons with disabilities and discussing universality and particularity in our understanding of assumed development and normalcy, it takes Finland, which has been chosen repeatedly as the happiest country in the world as its case- study. Using disability as a critical lens helps to demystify Finland that has the positive reputation of a Welfare State. By identifying different kinds of discrimination against persons with disabilities as well as successful examples of disability inclusion, it shows that when looking Finland from the perspective of persons with disabilities, inequality and poverty have been collective experiences of too many of them. It will be of interest to all scholars and students of disability studies, sociology, social policy, social work, political science, health and well-being studies and Nordic studies more broadly. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.
English
Keywords: Personal and public health / health education; Disability: social aspects; Politics and government; Sociology; Disability Studies; Wellbeing; Happiness; Nordic Model